Neighbourhood effects as a plant defence against ungulate herbivory - Koster, Bregje (2012)
For large herbivores patch selection is highly influenced by the presence of plant species and biomass that allows them the highest protein and energy intake. From the plant point of view browsing is seen as damage and loss of fitness and plants evolved different strategies to avoid or tolerate herbivory. Plant defence strategies can be from their own mechanical or chemical properties or can be obtained from neighbouring vegetation. Depending on the foraging strategy of the herbivore, the neighbourhood effect can be divided into 4 strategies: associational defence, associational susceptibility, neighbour contrast defence, or neighbour contrast susceptibility. The aim of this project is to gain a better understanding on the effect of neighbourhood quality (e.g. low or high palatability, habitat type) on browsing intensity of trees of different palatability. Two scales – habitat and tree scale were analyzed for this, using a natural gradient of palatability based on 5 tree species in the boreal zone of Sweden. At the habitat scale I found no evidence for an effect of neighbourhood quality, however at the tree scale there was a strong effect of neighbourhood quality for rowan and spruce. The results of this study suggested associational defence in the case of rowan (palatable species) and contrast defence for spruce (unpalatable species). The more average palatable species showed less effect of neighbourhood, suggesting the importance of the species palatability of the studied individual to which the neighbourhood belongs on the strength of this neighbourhood effect. Concluding, neighbourhood effects differ between foraging scales and tree species and are strongly influenced by the palatability of the focal trees. Due to a shift in palatability ranking along the latitudinal gradient the strength of the neighbourhood effect differs not only between species but also depends on the vegetation zone.